Civil-Military relations in South Asia - "Kukreja, Veena" (New Delhi, 1991)
This book contains following topics: Civil Military relations in Developing Countries; The military in Praetorian Pakistan; Three Military Regimes in Pakistan; Militarism in Bangladesh etc.
Keywords: Civil military relations Bangladesh